To cook or not to cook; international students' food choice strategy - Mustafa, Eshaby; Ideris, Muhamad Shah Kamal; Zainol, Noor Azimin (Global Academic Excellence, 2020)
The important role of food choices in symbolic, economic and social aspects of life leads to the increased attention given to this area. This role became increasingly important and complicated for international students living in a foreign country for the first time, away from their families, as they are now required to make individual decisions on food choice. Therefore, the food choice strategy as practiced by the international students will receive dedicated attention to this study. This study is set within the academic environment at a local university in Northern Malaysia. Several qualitative methods such as indepth interviews and observation were used to assess the international students’ food choice strategies and how the local food environment influences their food choice decision. Six international students took part in this study. The findings indicated that most international students resorted to preparing and cooking their own food, mainly to satisfy their cravings and as a cure to homesickness. The food choice strategy also depended on their level of knowledge in food preparation, convenience, and resources available to them. These finding advances the food choice decision process and explicates the food acculturation among international students in Malaysia. Moreover, the findings have direct implications for institutions’ management of international students in assisting and improving their overseas experience.